PENGARUH STRATEGI DIFERENSIASI TERHADAP KEUNGGULAN BERSAING RITEL MODERN (Kasus Hypermart Mall SKA Pekanbaru) - Nanda Fadilla; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Competition is a condition that can not be avoided by any company in its business. Fierce competition in industry will lead to any utilizing all resources to create a strong competitive advantage. One source of profits that can be optimized by the company to improve competitiveness is through the implementation of differentiation strategy. This study aimed to analyze the effect of the differentiation strategy on competitive advantage in the SKA Mall Hypermart Pekanbaru. The data used is primary data obtained by distributing questionnaires too 100 respondents that consumers who make purchase at the SKA Mall Hypermart Pekanbaru. While making the determination of the number respondents is by using sampling techniques accidental. Aspects of the measurement of the data analyzed done with the formation of indicators on eath statement submited by using the likert scale. In response interval between 1 (disagree) to 5 (strongly agree). Model analysis of the data used in this study using simple regression. The result found that indicators of differentiation strategy, namely product differentiation, service differentiation, personnel differentiation and differentiation image effect on competitive advantage at the SKA Mall Hypermart Pekanbaru. These findings indicate that companies can win the competition. Then it must be able to maintain a competitive advantage, namely the differentiation strategy.Keywords : Differentiation Strategy, Competitive Advantage